Reformasi Sistem Peradilan Pidana Indonesia Berwawasan Pancasila - Appludnopsanji; Hari Sutra Disemadi; Nyoman Serikat Putra Jaya (Fakultas Hukum, Universitas Warmadewa, 2021)
The condition of the Indonesian judiciary now reveals that the Indonesian criminal justice system is more inclined downward and obtuse and has been far from the existing justice in Pancasila values. This study will discuss regarding the current condition of the Indonesian criminal justice system and examine how the reform of the criminal Justice system will come with a vision of Pancasila. The research method described in this study uses normative legal research. The results showed that the weak condition of Indonesia's justice system now makes people distrust to find justice in it and has been far from the values of Pancasila. For this reason, reforms to the Indonesian criminal justice system that need to be guided by Pancasila can be started from the substance sub-system, structural sub-system, and cultural sub-system.